2005
DOI: 10.1093/ageing/afi202
|View full text |Cite
|
Sign up to set email alerts
|

Medication management at home: medication-related risk factors associated with poor health outcomes

Abstract: The findings support the theory that polypharmacy and medication-related risk factors as a result of polypharmacy are correlated to poor health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(146 citation statements)
references
References 13 publications
5
137
4
Order By: Relevance
“…Although the few number of studies including exclusively elderly patients would hinder drawing any conclusion regarding the increase of preventability of ADRs with age, this is in accordance with previous evidence about the challenge to ensure appropriate and safe use of medications among the elderly population (94,101 (207). Thus, interventions to prevent ADRs, implemented exclusively in hospital settings to target serious ADRs, would omit an important proportion of ADRs, which may be less serious but cause discomfort and worsen perceived quality of life of patients (29,30).…”
Section: Discussion Preventable Adverse Drug Reactions In Healthcare supporting
confidence: 84%
See 3 more Smart Citations
“…Although the few number of studies including exclusively elderly patients would hinder drawing any conclusion regarding the increase of preventability of ADRs with age, this is in accordance with previous evidence about the challenge to ensure appropriate and safe use of medications among the elderly population (94,101 (207). Thus, interventions to prevent ADRs, implemented exclusively in hospital settings to target serious ADRs, would omit an important proportion of ADRs, which may be less serious but cause discomfort and worsen perceived quality of life of patients (29,30).…”
Section: Discussion Preventable Adverse Drug Reactions In Healthcare supporting
confidence: 84%
“…Previous studies on DRMs, mainly conducted in emergency and inpatient settings, have found that ADRs and STEs are the most common DRMs (22)(23)(24)(25)(26)(27). DRMs have been associated with worsening of quality of life of patients (28)(29)(30), mortality (31)(32)(33), and increased costs for healthcare and society (20,34,35).…”
Section: Drug-related Morbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…75 An Australian study also found that having multiple prescribers increased patients' key medicationrelated risk factors and was associated with poor health outcomes. 76 Non-medical prescribing can lead to too many specialist health professionals, each prescribing medicines, without the oversight of a general practitioner. 77 General practitioners typically have a comprehensive and holistic approach to health and illness, which differentiates them from specialists.…”
Section: Issues With Expanded Roles For Pharmacistsmentioning
confidence: 99%